Doktrin Poros Maritim Dunia Era Jokowi dan Keamanan di Bidang Maritim Studi Kasus: Perdagangan Narkotika Jalur Laut Tahun 2014-2018 - Nur Hakiki; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2019)
Immediately after being elected in 2014, President Joko Widodo put forward the desire to makeIndonesia's sea territory the main policy focus. This is implemented by issuing the doctrine ofthe "Global Maritime Axis". President Jokowi also launched a development agenda focusingon five pillars, one of which concerns maritime security. Narcotics trafficking through the seais one of the various threats to maritime security in Indonesia. This is also exacerbated by thestatus of Indonesia which is called a narcotics emergency. This research aims to analyze theimpact of the "Global Maritime Axis" doctrine on maritime security, as seen from thedevelopment of cases of trafficking in narcotics through the sea that occurred in 2014 to 2018.This research uses the concept of maritime security in understanding the policies of PresidentJokowi's government in dealing with narcotics trafficking by sea. This research analyzes theimpact of the global maritime axis doctrine on government policies, both internal andinternational cooperation. The results of this research indicate that the policies issued by thegovernment have a positive influence, but are still not optimal in dealing with the problem oftrafficking in narcotics through the sea that occurred in the period of 2014 to 2018. This isbecause there are limitations in terms of facilities and infrastructure, the lack of coordinationbetween the parties involved, and the cooperation that is carried out mostly is still at an earlystage and has not shown significant results.